2017
DOI: 10.4103/ijdr.ijdr_8_16
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional, clinical study to evaluate mobility of teeth during pregnancy using periotest

Abstract: Pregnancy had a significant influence on tooth mobility. Highest value of tooth mobility was seen in the last month of pregnancy. The maximum severity of gingivitis was also seen during the third trimester of pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…Studies with a similar design have recorded the plaque index, among other things 11 , 42 , 43 , 44 , 45 , 46 , 47 , 48 . This provides information about the study participantʼs current oral hygiene.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with a similar design have recorded the plaque index, among other things 11 , 42 , 43 , 44 , 45 , 46 , 47 , 48 . This provides information about the study participantʼs current oral hygiene.…”
Section: Discussionmentioning
confidence: 99%
“…In another trial performed by Mishra et al [17], the link between female sex hormones, especially in gestation, and tooth mobility was confirmed. It was shown that the most substantial change in mobility occurred throughout the third trimester of pregnancy and most exclusively in the last month of gestation.…”
Section: Types Of Tooth Mobilitymentioning
confidence: 84%
“…The latter effect is of key importance for orthodontists and periodontologists, as the periodontium is made of—among others—the cortical plate of the alveolus with an adjoining scaffolding of cancellous bone trabeculae. Estrogen and progesterone receptors are also located in other periodontal components, namely, the gingiva and the periodontal ligaments [ 6 , 7 ], so it has already been proven that estrogen exerts a range of effects on tissues in the periodontium [ 8 , 9 , 10 ]. By regulating the production of epithelial glycogen, it reduces the keratinization of the gingiva, ultimately decreasing the role of the epithelial barrier.…”
Section: Introductionmentioning
confidence: 99%